Mindfulness-Based Coping With University Life: A Randomized Wait-List Controlled Study. (February 2018) - Lynch, Siobhán; Gander, Marie-Louise; Nahar, Ananda; Kohls, Niko; Walach, Harald
The benefits of mindfulness for a variety of clinical and nonclinical populations are well established and there is growing interest in the potential of mindfulness in higher education. This article reports on the results from a randomized wait-list controlled study of Mindfulness-Based Coping With University Life (MBCUL), an adaption of Mindfulness-Based Stress Reduction (MBSR) for university students. MBCUL is an 8-week program, which aims to help students bring mindful awareness to their academic work, stress management, approach to communication and relationships, and health. Participants were recruited from the general student body at the University of Northampton (United Kingdom) and were randomized into mindfulness or control groups. The mean age for students in the combined MBCUL group was M = 25.07, SD = 8.25 (18-50), and M = 28, SD = 7.26 (20-41) in the control group. A significant decrease in anxiety, F (1, 21) = 7.82, p = .01; depression, F (1, 22) = 4.15, p = .05; and perceived stress, F (1, 22) = 9.65, p = .01, was found in the MBCUL group compared with controls. Similarly, a significant increase in mindfulness was found in the MBCUL, F (1, 20) = 16.32, p = .001, compared with controls. Attrition was high, and the small numbers limit the generalizability of the data. However, the results suggest that MBCUL is an acceptable, useful mindfulness program for university students, which warrants further investigation with larger samples.